Comparison of different purification procedure for extraction of staphylococcal enterotoxin A from foods. - Niskanen, A (1976)
Different procedures commonly used for extraction, purification, and concentration of staphylococcal enterotoxins from foods were investigated with 131I- and 125I-labeled staphylococcal enterotoxin A. Loss of labeled enterotoxin A was compared with loss of total nitrogen. The results showed that in most of the common procedures, such as gel filtration, ion exchange, and heat treatment, the percentage of loss of labeled enterotoxin A was greater than the loss of total nitrogen. Chloroform extraction and acid precipitation with hydrochloric acid had nearly the same effect on the purification of both labeled enterotoxin A and total nitrogen. Ammonium sulfate precipitation proved to be practical and was successfully used for purification of enterotoxin A from sausage extract. Simultaneous use of trypsin and Pseudomonas peptidase for treatment of food extracts considerably reduced food proteins capable of interfering with serological detection of enterotoxins but did not essentailly influence the loss of enterotoxin A.